Assessment of Alcohol Use Disorder Risk Profile, Suicide Probability, and Cognitions in University Students - Çalışkan Pala, Seval; Eyüboğlu, Damla (Addicta: The Turkish Journal on Addictions, 2024)
The aim of the study was to determine the prevalence of high-risk alcohol use, suicide risk, and related fac- tors among university students in the Central Anatolian region of Türkiye. It is a cross-sectional study. The questionnaire used in the study consists of four parts. The first part consists of socio-demographic charac- teristics and related factors, the second part consists of the Addiction Profile Index Risk Scanning Scale, the third part consists of the Suicide Probability Scale, and the fourth part consists of the Brief Suicidal Cognitions Scale. The prevalence of high-risk alcohol use disorder among university students in the study group was found to be 27.2%. It was found that male students, those living at home with their friends, those who experienced a period of loss during university, those with suicidal individuals in the neighborhood, those with a high-risk profile for substance use, and those with low scores on the Social Support/Self Perception sub-domain of the Suicide Probability Scale were risk factors for a high-risk alcohol use profile. University students with high-risk alcohol use should be screened for suicidal ideation and cognition. In particular, program that focus on high-risk groups and aim to improve students’ healthy coping mechanisms should be expanded.
Keywords: Addiction to alcohol; alcohol use; suicide cognitions; suicide probability; university students